Lipid rescue reverses the bupivacaine-induced block of the fast Na+ current (INa) in cardiomyocytes of the rat left ventricle - Wagner, Michael; Zausig, York A.; Ruf, Simone; Rudakova, Elena; Gruber, Michael; Graf, Bernhard M.; Volk, Tilmann (Anesthesiology, 2014)
Cardiovascular resuscitation upon intoxication with lipophilic ion channel-blocking agents has proven most difficult. Recently, favorable results have been reported when lipid rescue therapy is performed, i.e., the infusion of a triglyceride-rich lipid emulsion during resuscitation. However, the mechanism of action is poorly understood.The authors investigate the effects of a clinically used lipid emulsion (Lipovenös® MCT 20%; Fresenius Kabi AG, Bad Homburg, Germany) on the block of the fast Na current (INa) induced by the lipophilic local anesthetic bupivacaine in adult rat left ventricular myocytes by using the whole cell patch clamp technique.Bupivacaine at 10 µm decreased INa by 54% (-19.3 ± 1.9 pApF vs. -42.3 ± 4.3 pApF; n = 17; P < 0.001; VPip = -40 mV, 1 Hz). Addition of 10% lipid emulsion in the presence of bupivacaine produced a 37% increase in INa (-26.4 ± 2.8 pApF; n = 17; P < 0.001 vs. bupivacaine alone). To test whether these results could be explained by a reduction in the free bupivacaine concentration by the lipid (lipid-sink effect), the authors removed the lipid phase from the bupivacaine-lipid mixture by ultracentrifugation. Also, the resulting water phase led to an increase in INa (+19%; n = 17; P < 0.001 vs. bupivacaine), demonstrating that part of the bupivacaine had been removed during ultracentrifugation. The substantially less lipophilic mepivacaine (40 µm) reduced INa by 27% (n = 24; P < 0.001). The mepivacaine-lipid mixture caused a significant increase in INa (+17%; n = 24; P < 0.001). For mepivacaine, only a small lipid-sink effect could be demonstrated (+8%; n = 23; P < 0.01), reflecting its poor lipid solubility.The authors demonstrate lipid rescue on the single-cell level and provide evidence for a lipid-sink mechanism.
EVALuna2:4497